Democratic capacities for the governance of protected natural areas. Case: natural reserve Salinas and aguada blanca (2015 - 2017) - Mayo D’Arrigo, Maritza Jesús (2019)
Protected natural areas are spaces that have a valuable ecosystemic, genetic and biological heritage and in which cultural and ethnic diversity provides valuable traditional knowledge regarding their uses and properties. Managing these areas implies recognizing that they are multicultural spaces where actors with multiple interests converge; it also requires that not only be guaranteed that all those involved are represented in the management instances, but also that everyone has the necessary capacities to participate actively in the decision-making process. What are those capacities that allow the participation of all under equal conditions? The study identifies ten capacities, which are called “democratic capacities”; and it is analyzed if these are present in the actors involved in the management of the National Reserve of Salinas and Aguada Blanca in the period 2015-2017. The study concludes that the capacities for dialogue and intercultural management are well developed. While the abilities: reading ability; management of the language of the communities; attitude and willingness to provide information permanently; surrounding analysis; decision making; conflict resolution; and incidence have a medium development, and there are still weaknesses in the capacity to comply with the agreements.